2019
DOI: 10.21577/0103-5053.20190084
|View full text |Cite
|
Sign up to set email alerts
|

Are Imidazoles Versatile or Promiscuous in Reactions With Organophosphates? Insights From the Case of Parathion

Abstract: Is the broad mechanistic versatility of imidazole towards organophosphates (OPs), that has inspired many catalysts and sensors, beneficial? Herein, a thorough analysis is given seeking to unravel this puzzle. For OPs from the P=O family, imidazole attacks the phosphorus atom exclusively (N-phosphorylates). With the P=S family which are less reactive, an unusual N-alkylation predominates. Surprisingly, imidazole reacts with methyl parathion exclusively at the aliphatic carbon, whilst for the ethylated analogue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…[63] Another study investigated the reaction kinetics of IMZ with Parathion and Methyl parathion in aqueous solution by NMR, mass spectrometry, kinetics and theoretical calculations. [64,65] In these cases, the kinetics followed by UV-vis spectroscopy present unexpected results (Figure 17), since the expected Red lines represent fitting between kinetic data and Catalan's paramethers [62] using multiple regression. B. TSSs and energy barriers (kcal mol À 1 ) for the reactions of both tautomers of 4(5) HMZ with DEDNPP obtained at B3LYP/6-31 + G(d, p) level of theory.…”
Section: Reactions With P=s Organophosphatesmentioning
confidence: 94%
See 3 more Smart Citations
“…[63] Another study investigated the reaction kinetics of IMZ with Parathion and Methyl parathion in aqueous solution by NMR, mass spectrometry, kinetics and theoretical calculations. [64,65] In these cases, the kinetics followed by UV-vis spectroscopy present unexpected results (Figure 17), since the expected Red lines represent fitting between kinetic data and Catalan's paramethers [62] using multiple regression. B. TSSs and energy barriers (kcal mol À 1 ) for the reactions of both tautomers of 4(5) HMZ with DEDNPP obtained at B3LYP/6-31 + G(d, p) level of theory.…”
Section: Reactions With P=s Organophosphatesmentioning
confidence: 94%
“…By another perspective, the neutralization process of unwanted stockpiles of Methyl parathion, for example, can be used as a source for synthesizing alkylimidazoles. [65] Table 1 presents a summary of the results for the reactions of IMZ with the family of Parathion and Paraoxon. According to the results we could rationalize that methyl group and sulfur atom drive the reaction to the aliphatic group and the oxygen [65] and (c) Paraoxon (pH 8.98; 25 °C) [55] with IMZ in aqueous solution.…”
Section: Reactions With P=s Organophosphatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among different catalysts, materials based on imidazole (IMZ) and its derivatives have shown excellent behavior in the detoxification of OPs [19], biomimicking the histidine imidazole in the protein phosphorylation [20,21]. The histidine imidazole in protein enzymes is the most versatile catalytic group, with a pKa near 7, it can act as an acid, base or nucleophilic catalyst [22,23]. Several studies confirmed that cleavage of phosphate esters can be catalyzed by the presence of IMZ, with catalytic increments around 10 5 -fold [10,14,22], combined with the advantages of complete regeneration of the initial catalyst and formation of less toxic compounds.…”
Section: Introductionmentioning
confidence: 99%